2019
DOI: 10.1109/access.2019.2943191
|View full text |Cite
|
Sign up to set email alerts
|

A Periodic Potential Underdamped Stochastic Resonance Method and Its Application for Gear Fault Diagnosis

Abstract: The vibration feature of weak gear fault is often covered in strong background noise, which makes it necessary to establish weak feature enhancement methods. Among the enhancement methods, stochastic resonance (SR) has the unique advantage of transferring noise energy to weak signals and has a great application prospection in weak signal extraction. But the traditional SR potential model cannot form a richer potential structure and may lead to system instability when the noise is too great. To overcome these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…proposed a periodic potential underdamping stochastic resonance (PPUSR) in the paper and used PPUSR to extract the characteristics of the gearbox vibration signals. The results showed that the proposed method can detect gear wear faults and tooth broken faults [14]. In the research of Li Y.B.…”
Section: Introductionmentioning
confidence: 92%
“…proposed a periodic potential underdamping stochastic resonance (PPUSR) in the paper and used PPUSR to extract the characteristics of the gearbox vibration signals. The results showed that the proposed method can detect gear wear faults and tooth broken faults [14]. In the research of Li Y.B.…”
Section: Introductionmentioning
confidence: 92%
“…Then, QGAs are used to optimize the parameters pairs (a, b, α, β, m) of the improved UABSR method with the asymmetric bistable potential shown in Eq. (7). According the improved UABSR method in Section 2.4, the adaptive diagnosis result of the proposed method is displayed in Fig.…”
Section: Simulation Verificationmentioning
confidence: 99%
“…In addition, the fault location of the spindle bearing and the range of the fault characteristic frequency are usually unknown in advance. For above reasons, it is necessary to effectively diagnose the fault and estimate the running state of spindle bearings, so as to recognize the principle of spindle bearing operation, optimize the bearing design, avoid unscheduled downtime and reduce the maintenance cost [4]- [7].…”
Section: Introductionmentioning
confidence: 99%
“…Other works combine acoustic and vibration measurements for gear fault diagnosis [19]. Li et al propose the technique of periodic potential underdamped stochastic resonance to provide gear fault diagnosis from acoustic measurements in environments of high environmental noise [20]. Techniques of unsupervised machine learning have been applied to the detection of gear box bearing faults in environments of heavy background noises [21].…”
Section: Analysis Of the Current System And Specification Of The Smentioning
confidence: 99%